Dependence of plasma focus argon soft X-Ray yield on storage energy, total and pinch currents - Akel, M.; Lee, S. (Springer US, 2012)
Numerical experiments are carried out systematically to determine the argon soft X-Ray yield Ysxr for optimized argon plasma focus with storage energy E0 from 1 kJ to 1 MJ. The ratio c = b/a, of outer to inner radii; and the operating voltage V0 are kept constant. E0 is varied by changing the capacitance C0. These numerical experiments were investigated on argon plasma focus at different operational gas pressures (0.41, 0.75, 1, 1.5, 2.5 and 3 Torr) for two different values of static inductance L0 (270 and 10 nH). Scaling laws on argon soft X-Ray yield, in terms of storage energies E0, peak discharge current Ipeak and focus pinch current Ipinch were found. It was found that the argon X-ray yields scale well with Ysxr=8×10−11I4.12pinchYsxr=8×10−11Ipinch4.12 for the high inductance (270 nH) and Ysxr=7×10−13I4.94pinchYsxr=7×10−13Ipinch4.94 for the low inductance (10 nH), (where yields are in joules and current in kilo amperes). While the soft X-ray yield scaling laws in terms of storage energies were found to be as Ysxr=0.05×E0.940Ysxr=0.05×E00.94 at energies in the 1–100 kJ region. The scaling ‘drops’ as E0 is increased, and Ysxr scales as Ysxr=1.01×E0.330Ysxr=1.01×E00.33 at high energies towards 1 MJ for 10 nH at argon gas pressure of 1 Torr. The optimum efficiencies for SXR yield were found to be 0.00077% with a capacitor bank energy of 112.5 kJ for high inductance (270 nH) and 0.005% with a capacitor bank energy of 4.5 kJ for low inductance (10 nH). Therefore for larger devices, it may be necessary to operate at a higher voltage and use higher driver impedance to ensure increasing X-ray yield efficiency beyond the optimum values. As storage energy is changed the required electrode geometry for optimum yield is obtained and the resultant plasma pinch parameters are found. Required values of axial speed for argon soft X-ray emission were found to be in the range 11–14 cm/μs.